Performances: l'art en action - Goldberg, RoseLee; Anderson, Laurie (Thames & Hudson, 1999)
Dresse un panorama complet des arts vivants depuis 1960 : happenings, théâtre et opéra d'avant-garde, danse contemporaine, art vidéo, installations multimédias. Yves Klein, Joseph Beuys, Robert Wilson, Tadeusz Kantor, Pina Bausch, Gilbert & George, Philippe Decouflé, entre autres, sont évoqués. L'ouvrage est illustré d'oeuvres européennes, américaines, japonaises et australiennes.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; arts; asie; australie; corps; cours; discipline; europe; har4600; histoire de l'art; japon; océanie; premier cycle; périodes historiques; régions géographiques; thématiques; états-unis

Une organisation maternaliste au Québec la Fédération nationale Saint-Jean-Baptiste et la bataille pour le vote des femmes - Hébert, Karine (Revue d'histoire de l'Amérique française, 1999)
Cet article présente, à la lumière des développements récents de l'historiographie féministe, une nouvelle interprétation de la Fédération nationale Saint-Jean-Baptiste. Cette réinterprétation se base sur un concept assez nouveau: le maternalisme, défini comme une catégorie d'analyse utilisée pour qualifier les mouvements de femmes chez qui la maternité constituait le point central de l'idéologie et de l'argumentation. Nous examinons, entre autres, le modèle féminin véhiculé par la FNSJB pour constater qu'il correspondait au modèle traditionnel de « la femme », celui qui effectuait une équation entre la femme et la mère. La maternité n'était toutefois pas perçue par la FNSJB comme une fonction limitative, mais bien comme une ouverture vers la société. Elle a donc dû redéfinir les frontières entre les sphères privée et publique pour permettre aux femmes de transgresser celles du foyer et faire bénéficier la société de leur influence maternelle. Le cadre d'analyse élaboré dans la première partie est ensuite appliqué à un cas concret de revendication: la bataille pour le vote des femmes.
https://www.erudit.org/en/journals/haf/1999-v52-n3-haf219/005467ar/
Keywords: 1900-1909; 1900-1999; 1910-1919; amériques; approches et analyses; canada; changement social; corps; cours; droit de vote; fem1000; histoire des femmes*; histoire et politique; maternité; militance; mouvements féministes; patriarcat; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

Performing the body: performing the text - Jones, Amelia..; Stephenson, Andrew; Jones, Amelia; Stephenson, Andrew (Routledge, 1999)
This book explores the new performativity in art theory and practice, examining ways of rethinking interpretive processes in visual culture. Since the 1960s, visual art practices - from body art to minimalism - have taken contemporary art outside the museum and gallery; by embracing theatricality and performance and exploding the boundaries set by traditional art criticism. The contributors argue that interpretation needs to be recognised as much more dynamic and contingent. Offering its own performance script, and embracing both canonical fine artists such as Manet, De Kooning and Jasper Johns, and performance artists such as Vito Acconci and Gunter Brus, this book offers radical re-readings of art works and points confidently towards new models for understanding art.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; premier cycle; périodes historiques; thématiques

Is multiculturalism bad for women? - Okin, Susan Moller; Cohen, Joshua (Princeton University Press, 1999)
Polygamy, forced marriage, female genital mutilation, punishing women for being raped, differential access for men and women to health care and education, unequal rights of ownership, assembly, and political participation, unequal vulnerability to violence. These practices and conditions are standard in some parts of the world. Do demands for multiculturalism—and certain minority group rights in particular—make them more likely to continue and to spread to liberal democracies? Are there fundamental conflicts between our commitment to gender equity and our increasing desire to respect the customs of minority cultures or religions? In this book, the eminent feminist Susan Moller Okin and fifteen of the world’s leading thinkers about feminism and multiculturalism explore these unsettling questions in a provocative, passionate, and illuminating debate. Okin opens by arguing that some group rights can, in fact, endanger women. She points, for example, to the French government’s giving thousands of male immigrants special permission to bring multiple wives into the country, despite French laws against polygamy and the wives’ own bitter opposition to the practice. Okin argues that if we agree that women should not be disadvantaged because of their sex, we should not accept group rights that permit oppressive practices on the grounds that they are fundamental to minority cultures whose existence may otherwise be threatened. In reply, some respondents reject Okin’s position outright, contending that her views are rooted in a moral universalism that is blind to cultural difference. Others quarrel with Okin’s focus on gender, or argue that we should be careful about which group rights we permit, but not reject the category of group rights altogether. Okin concludes with a rebuttal, clarifying, adjusting, and extending her original position. These incisive and accessible essays—expanded from their original publication in Boston Review and including four new contributions—are indispensable reading for anyone interested in one of the most contentious social and political issues today.
Keywords: 1900-1999; 1990-1999; amérique du nord; amériques; approches et analyses; corps; cours; discipline; droits des femmes*; europe; france; multiculturalisme; phi4336; philosophie; premier cycle; périodes historiques; racisme; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; états-unis

Les paradoxes des droits reproductifs au Brésil: avortement et stérilisation féminine - Scavone, Lucila; Bateman, Simone; Le Doaré, Hélène (Cahiers du Genre, 1999)
Cet article rend compte du débat mené au Brésil autour des droits reproductifs et souligne les avancées et les contradictions particulières de deux problèmes que rencontrent actuellement les femmes brésiliennes : la stérilisation et la pratique illégale de l’avortement. Il met en évidence que la pratique généralisée de la stérilisation féminine et le nombre des avortements clandestins, qui représentent un risque pour la santé des femmes, révèlent les carences de la politique de la santé sur le plan des choix reproductifs et de la politique de contrôle démographique. Il montre les diverses orientations prises par ce débat à la fin des années quatre-vingt-dix et la nécessité de se réapproprier sa dynamique de transformation sociale.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du sud; approches et analyses; brésil; corps; cours; discipline; discours dominant; droits des femmes*; justice reproductive; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

Techniques et acteurs: parcours différenciés de femmes dans une démarche de fécondation in vitro - Tain, Laurence (Cahiers du Genre, 1999)
L’analyse des relations entre acteurs des nouvelles techniques de reproduction a souvent conduit à privilégier la description des stratégies de ceux qui sont désignés comme dominants : les inventeurs, les médecins, les hommes. A l’inverse, on s’intéressera ici à l’expérience des femmes en faisant l’hypothèse qu’il existe des différenciations dans la démarche de procréation médicalement assistée à l’image de la complexité des rapports sociaux de sexe. Effectivement, l’analyse des parcours de femmes, à partir des dossiers médicaux d’un service hospitalier spécialisé, révèle des lignes de conduite spécifiques : sont ainsi mises à jour des stratégies différentes selon la situation professionnelle, le niveau de qualification, la position vis-à-vis de l’hôpital. Avec la médicalisation croissante de notre société, le « devoir de procréation » se jouerait donc sur une scène où interviennent conjointement les rapports sociaux de sexe, la position vis-à-vis du travail, le lien avec l’institution médicale.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; angleterre; approches et analyses; corps; corps des femmes; cours; discipline; europe; france; inégalités; justice reproductive; maternité; postmodernisme; premier cycle; privilèges; procréation; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques

L’individualité féminine à l’épreuve des technologies de reproduction - Van der Ploeg (Cahiers du Genre, 1999)
Cet article décrit l’émergence de deux nouveaux types de patients, le couple et le fœtus, dans certaines techniques reproductives telles la fécondation in vitro et la chirurgie fœtale. Il montre comment l’émergence de ces patients, comme des entités traitables, est liée au développement de ces technologies. Ces pratiques médicales effacent en partie les distinctions entre le naturel et le technique, entre un individu et un autre, et sont accompagnées de dispositifs discursifs spécifiques qui rendent acceptable, voire même naturel ou inévitable le fait de traiter les problèmes de l’enfant ou de l’homme au moyen d’interventions sur le corps de la femme. Cet article est consacré à l’analyse et à la déconstruction de ces dispositifs.
Number: 25
Keywords: 1900-1999; 1990-1999; approches et analyses; corps; corps des femmes; cours; discipline; discours dominant; europe; france; maternité; postmodernisme; premier cycle; procréation; périodes historiques; régions géographiques; santé; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques

Femmes au miroir: une histoire de l'autoportrait féminin - Borzello, Frances (Thames & Hudson, 1998)
Une sélection d'autoportraits féminins empruntés à toute l'histoire de l'art, de la religieuse anonyme qui glissa son effigie dans la lettrine d'un manuscrit du XIIe siècle à Cindy Sherman et ses photogrammes révélateurs des visions stéréotypées de la femme, en passant par Sofonisba Anguissola, Artemisia Gentileschi, Elisabeth Vigée-Lebrun, Frida Kahlo, Hannah Wilke, etc.
Section: 224 pages : illustrations ; 29 cm
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; moyen-âge; premier cycle; périodes historiques; thématiques

Body art: performing the subject - Jones, Amelia (University of Minnesota Press, 1998)
An examination of the social and cultural significance of body art by a major new voice. The past few years have seen an explosion of interest in body art, in which the artist's body is integral to the work of art. With the revoking of NEA funding for such artists as Karen Finley, Tim Miller, and others, public awareness and media coverage of body-oriented performances have increased. Yet the roots of body art extend to the 1960s and before. In this definitive book, Amelia Jones explores body art projects from the 1960s and 1970s and relates their impact to the work of body artists active today, providing a new conceptual framework for defining postmodernism in the visual arts. Jones begins with a discussion of the shifting intellectual terrain of the 1950s and 1960s, focusing on the work of Ana Mendieta. Moving to an examination of the reception of Jackson Pollock's "performative" acts of painting, she argues that Pollock is a pivotal figure between modernism and postmodernism. The book continues with explorations of Vito Acconci and Hannah Wilke, whose practices exemplify a new kind of performance that arose in the late 1960s, one that represents a dramatic shift in the conception of the artistic subject. Jones then surveys the work of a younger generation of artists – including Laurie Anderson, Orlan, Maureen Connor, Lyle Ashton Harris, Laura Aguilar, and Bob Flanagan – whose recent work integrates technology and issues of identity to continue to expand the critique begun in earlier body art projects. Embracing an exhilarating mix of methodologies and perspectives (including feminism, queer theory, philosophy, psychoanalysis, and literary theory), this rigorous and elegantexamination of body art provides rich historical insight and essential context that rethinks the parameters of postmodern culture.
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; approches et analyses; art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; performance; philosophie; postmodernisme; premier cycle; périodes historiques; queer; sciences humaines; sexualité; thématiques; théorie de l'art

Lessons from the intersexed - Kessler, Suzanne J. (Rutgers University Press, 1998)
From the moment intersexuality-the condition of having physical gender markers (genitals, gonads, or chromosomes) that are neither clearly female nor male-is suspected and diagnosed, social institutions are mobilized in order to maintain the two seemingly objective sexual categories. Infants' bodies are altered, and what was "ambiguous" is made "normal." Kessler's interviews with pediatric surgeons and endocrinologists reveal how the intersex condition is normalized for parents and she argues that the way in which intersexuality is managed by the medical and psychological professions displays our culture's beliefs about gender and genitals. Parents of intersexed children are rarely heard from, but in this book they provide another perspective on reasons for genital surgeries and the quality of medical and psychological management. Although physicians educate parents about how to think about their children's condition, Kessler learned from parents of intersexed children that some parents are able to accept atypical genitals. Based on analysis of the medical literature and interview with adults who had received treatment as interesexed children, Kessler proposes new approaches for physicians to use in talking with parents and children. She also evaluates the appearance of a politicized vanguard, many of who are promoting an intersexual identity, who seek to alter the way physicians respond to intersexuality. Kessler explores the possibilities and implications of suspending a commitment to two "natural" genders and addresses gender destabilization issues arising from intersexuality. She thus compels readers to re-think the meaning of gender, genitals, and sexuality.
Section: x, 193 pages : illustrations ; 22 cm
Keywords: LGBTQIA2+; approches et analyses; capacitisme; care; corps; cours; discipline; ethnographie; intersexuation; premier cycle; psychologie; santé; sciences humaines; soc2014; système de genre; systèmes d'oppressions; thématiques; violences; violences médicales

Les limites de l'identité sexuelle - Lamoureux, Diane (Les éditions du remue-ménage, 1998)
Les études de Michel Foucault sur la sexualité et son histoire, de même que les premiers travaux de Judith Butler sur la fluidité des postures de genre, ont contribué à l’émergence de la pensée queer, qui récuse le fixisme identitaire sans pour autant rejeter la notion d’identité. Ce courant de pensée a eu des répercussions tant dans le domaine des études féministes que dans celui des études LGBT ou encore des études sur les sexualités qui s’intéressent aux marges de la société hétérosexiste. Au-delà des oppositions binaires du masculin et du féminin ou de l’hétérosexualité et de l’homosexualité, il y a toujours un indécidable, qui résiste à la bipartition, une zone de flou, d’hybride et de poreux. C’est cet indécidable qui force la réflexion, non pas pour le faire entrer dans une catégorie d’opposition binaire, mais pour faire rebondir la pensée. Des textes de Carmen Gill, Ross Higgins, Diane Lamoureux, Marie-José Nadal, Tania Navarro Swain, Paul-André Perron, Robert Schwartzwald et Colette St-Hilaire.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; europe; fem1000; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; québec; régions géographiques; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques

Le sexe biologique et sa relation au sexe social - Peyre, Evelyne; Wiels, Joëlle (Les Temps modernes, 1997)
http://transidentite.free.fr/oms/peyre_wiels-les_temps_modernes1997.pdf
Keywords: anthropologie; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; genre; identités LGBTQIA2+; lit2815; lit3220; lit3495; premier cycle; ressource en ligne; sciences humaines; sexe biologique; thématiques

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Engels et l'émancipation des femmes - Europe Solidaire Sans Frontières - Trat, Josette (Engels et savants révolutionnaires, 1997)
Keywords: 1800-1899; 1900-1909; 1900-1999; 1970-1979; approches et analyses; capitalisme; classe ouvrière; corps; cours; discipline; europe; famille; france; justice sociale; marxisme; premier cycle; périodes historiques; russie; régions géographiques; sciences humaines; sexisme; soc1016; sociologie; systèmes d'oppressions; thématiques; travail

An intimate distance: women, artists and the body - Betterton, Rosemary.. (Routledge, 1996)
How have women artists taken possession of the female body? What is the relationship between looking and embodiment in art made by women? In a series of original readings of the work of artists from Kathe Kollwitz and Georgia O'Keeffe to Helen Chadwick and Laura Godfrey-Isaacs, Rosemary Betterton explores how women artists have addressed the changing relationship between women, the body and its representation in art. In detailed critical essays that range from the analysis of maternal imagery in the work of German artists at the turn of the century to the unrepresented body in contemporary abstract painting, Betterton argues that women's art practices offer new ways of engaging with our fascinations with and fears about the female body. Reflecting the shift within feminist art over the last decade, An Intimate Distance sets the reinscription of the body within women's art practice in the context of current debates on the body, including reproductive science, maternal subjectivity and the concept of 'body horror' in relation to food, ageing and sex. Drawing on recent theories of embodiment developed within feminist philosophy and psychoanalytic theory, the essays reveal how the permeable boundaries between nature and culture, the female body and technology are being crossed in the work of women artists.
Keywords: 1900-1999; approches et analyses; art contemporain; artistes féministes; arts; corps; cours; discipline; europe; femmes* artistes; féminisme pop; har4600; histoire de l'art; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques

Bisexualité: le dernier tabou - Mendès-Leite, Rommel; Deschamps, Catherine; Proth, Bruno-Marcel (Calmann-Lévy, 1996)
A partir de nombreux témoignages, ce livre dresse un portrait des bisexuels dans leur infinie variété, leur histoire, leur quotidien.
Section: 279 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; inégalités; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

The art of reflection: women artists'self-portraiture in the twentieth century - Meskimmon, Marsha.. (Columbia University Press, 1996)
Self-portraiture has long been a means for the male artist to assert an identity as masterful creator or tortured soul; women have overwhelmingly been presented as objects, and rarely as subjects of self-portraiture. In recent years, however, women artists have used their work to disrupt this tradition. With 43 illustrations of works by Louise Bourgeois, Frida Kahlo, Alice Neel, Cindy Sherman, and Jo Spence, among others, The Art of Reflection is the first sustained inquiry into the appropriation of self-portraiture by women. In suggestive critical meditations on paintings, photographic work, sculpture, performance art, and body art, Marsha Meskimmon shows how twentieth-century women artists have undermined male-centered definitions of how "the artist" depicts the self. Drawing upon feminist theory and philosophy from Simone de Beauvoir to Luce Irigaray, The Art of Reflection casts doubt on the idea of self-portrait as a mirror, in which the static self is rendered accurately and naturalistically. Meskimmon evokes a series of myths about what an artist is, how "he" should be represented, and how "his" work is to be read as autobiography. Through close readings of the imaginative self-representations of women artists -as male artist and god, as central player in the studio and in the Christian passion- she shatters these myths. In an absorbing assessment of the ways women artists have negotiated the complex group of roles ascribed to "woman," Meskimmon considers the partially nude painting by pregnant artist Paula Modersohn-Becker and performance artist Annie Sprinkle's confrontation of the thin line between celebration of female sexuality and objectification of the female body. As a nuanced appreciation of the interpretations of self-portraiture among women artists, The Art of Reflection will prove an invaluable resource on a subject that has received little attention from art criticism. Meskimmon's work also presents a bold challenge to critical tradition, compelling readers to rethink the meaning of the genre as a whole.
Keywords: 1900-1999; arts; corps; cours; critique d'art; discipline; femmes* artistes; har4600; histoire de l'art; premier cycle; périodes historiques; représentation; thématiques

Generations & geographies in the visual arts: feminist readings - Pollock, Griselda.. (Routledge, 1996)
In Generations and Geographies, the challenge of contemporary feminist theory encounters the provocation of the visual arts made by women in the twentieth century. The major issue is difference: sexual, cultural and social. Generations points to the singularity of each artist's creative negotiation of time and historical and political circumstance; Geographies calls attention to the significance of place, location and cultural diversity, connecting issues of sexuality to those of nationality, imperialism, migration, diaspora and genocide.Generations and Geographies is framed by theoretical debates in cultural analysis by Griselda Pollock, Mieke Bal, Elisabeth Bronfen and Irit Rogoff, and two historical analyses of representations of the female nude by Rosemary Betterton and Nanette Salomon. Essays on international contemporary art discuss artistic practice by women working in both western and non-western contexts, focusing on themes of the mother, the body, the land and history/memory. The artists discussed include the French performance artist Orlan, the Cuban American artist Ana Mendieta and Jenny Saville from Britain, the Chilean artist Cecilia Vicuna, Shimada Yoshiko from Japan, the Korean artist Re-Hyun Park and the Korean/Canadian artist Jin-me Yoon, Bracha Lichtenberg Ettinger from Israel and the American artist Cindy Sherman. British/Zanzibari artist Lubaina Himid provides specially commissioned artists' pages on the theme of history, location and displacement.
Keywords: 1900-1999; approches et analyses; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; histoire et politique; intersectionnalité; maternité; point de vue situé; premier cycle; périodes historiques; ressource en ligne; thématiques

The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Les relations amoureuses entre les femmes du XVIe au XXe siècle. Essai historique. - Bonnet, Marie-Joe (Odile Jacob, 1995)
Voici la première histoire de l'amour entre les femmes qui, sur cinq siècles, de la Renaissance à nos jours, tienne compte à la fois du regard extérieur des hommes et de l'approche des lesbiennes elles-mêmes. Pour la première fois, aussi, une analyse à long terme est proposée qui dégage une évolution des moeurs, des mentalités et de la place des femmes dans la société. Jusqu'à présent, en effet, l'histoire des femmes occultait l'amour entre femmes, alors que les lesbiennes ont joué un rôle prépondérant dans les mouvements progressistes politiques et artistiques. Unique en son genre par son érudition, son approche pluridisciplinaire, ses mises en perspective originales et la période considérée, cet essai s'impose déjà comme un ouvrage de référence.
Première publication: 1981
Keywords: approches et analyses; corps; cours; cycles supérieurs; discipline; droits des femmes*; europe; fem1000; fem7000; france; histoire; histoire des femmes*; histoire et politique; hétérosexisme; identités; identités LGBTQIA2+; invisibilités; lesbianisme; lit3220; premier cycle; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Sexy bodies: the strange carnalities of feminism - Grosz, E. A.; Probyn, Elspeth (Routledge, 1995)
Are bodies sexy? How? In what sorts of ways? Sexy Bodies investigates the production of sexual bodies and sexual practices, of sexualities which are dyke, bi, transracial, and even hetero. It celebrates lesbian and queer sexualities but also explores what runs underneath and within all sexualities, discovering what is fundamentally weird and strange about all bodies, all carnalities. Looking at a pleasurable variety of cultural forms and texts, the contributors consider the particular charms of girls and horses, from National Velvet to Marnie; discuss figures of the lesbian body from vampires to tribades to tomboys; uncover 'virtual' lesbians in the fiction of Jeanette Winterson; track desire in the music of legendary Blues singers; and investigate the ever-scrutinised and celebrated body of Elizabeth Taylor. The collection includes two important pieces of fiction by Mary Fallon and Nicole Brossard. Sexy Bodies makes new connections between and amongst bodies, cruising the borders of the obscene, the pleasurable, the desirable and the hitherto unspoken rethinking sexuality anew as deeply and strangely sexy.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; féminisme pop; identités LGBTQIA2+; lesbianisme; lit4700; premier cycle; queer; ressource en ligne; sexualité; thématiques

XXX: a woman's right to pornography - McElroy, Wendy (St. Martin's Press, 1995)
An unconventional argument for the preservation of pornography asserts that pornography can serve to benefit the feminist movement and promote sexual freedom for women, and explores the historical relationship between women and pornography.
Section: xi, 243 pages ; 22 cm
Keywords: corps; cours; droits des femmes*; pornographie; premier cycle; sex1911; sexualité; thématiques

Of woman born: Motherhood as experience and institution - Rich, Adrienne (Norton, 1995)
Adrienne Rich's influential and landmark investigation concerns both the experience and the institution of motherhood. The experience is her own—as a woman, a poet, a feminist, and a mother—but it is an experience determined by the institution, imposed on all women everywhere. She draws on personal materials, history, research, and literature to create a document of universal importance. Dans Of Woman Born , initialement publié en 1976, la poétesse et féministe influente Adrienne Rich examine les systèmes patriarcaux et les institutions politiques qui définissent la maternité. En explorant sa propre expérience - en tant que femme, poète, féministe et mère - elle trouve que l'acte de materner est à la fois déterminé par et distinct de l'institution de la maternité telle qu'elle est imposée à toutes les femmes partout dans le monde
Première édition: 1976
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; corps; cours; discours dominant; fem1000; maternité; premier cycle; périodes historiques; régions géographiques; santé; systèmes d'oppressions; thématiques; théories féministes; états-unis

New feminist criticism: art, identity, action - Frueh, Joanna; Langer, Cassandra; Raven, Arlene; Frueh, Joanna; Langer, Cassandra; Raven, Arlene (IconEditions, 1994)
This anthology of fifteen timely articles offers a wide range of feminist criticism sparked by ideas and events of the 1980's and 1990's. The articles consider culture, language, race, identity, sexuality, gender, creativity, aging and other issues. Though different in methodology, the writings are united by their common interest in feminism as a vehicule for intellectual exploration and individual communication and understanding. In their revisionary approaches, the contributors offer exciting new insights into the complex interaction between women and cultures, questionning inclusion as well as exclusion. "New Feminist Criticism" presents the unfinished and ongoing agenda of feminism in art, society and culture.
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; art contemporain; art féministe; arts; corps; cours; critique d'art; discipline; har4600; histoire de l'art; histoire et politique; identités LGBTQIA2+; intersectionnalité; premier cycle; périodes historiques; race; thématiques; vieillesse

Volatile bodies: toward a corporeal feminism - Grosz, E. A. (Indiana University Press, 1994)
Volatile Bodies demonstrates that the sexually specific body is socially constructed: biology or nature is not opposed to or in conflict with culture. Human biology is inherently social and has no pure or natural "origin" outside of culture. Being the raw material of social and cultural organization, it is "incomplete" and thus subject to the endless rewriting and social inscription that constitute all sign systems. Examining the theories of Freud, Lacan, Merleau-Ponty, Foucault, Deleuze, Derrida, etc. on the subject of the body, Elizabeth Grosz concludes that the body they theorize is male. These thinkers are not providing an account of "human" corporeality but of male corporeality. Grosz then turns to corporeal experiences unique to women–menstruation, pregnancy, childbirth, lactation, menopause. Her examination of female experience lays the groundwork for developing theories of sexed corporeality rather than merely rectifying flawed models of male theorists.
Section: xvi, 250 pages
Keywords: approches et analyses; corps; cours; discipline; discours dominant; lit4700; premier cycle; sciences humaines; sociologie; systèmes d'oppressions; thématiques; études culturelles

L'illusion transsexuelle - Mercader, Patricia (L'Harmattan, 1994)
Naît-on transsexuel ou le devient-on? Quel est le sexe des transsexuels? Peut-on parler de droit à l'identité sexuelle?.... En confrontant les points de vue des acteurs sociaux engagés dans le "phénomène transsexuel" (médecins, psychanalistes, sociologues, juristes et bien sûr les transsexuels eux-mêmes), cela éclaire les enjeux de société que traduisent ces questions profondément éthiques.
Section: 297 pages
Keywords: 1900-1999; 1980-1989; 1990-1999; LGBTQIA2+; approches et analyses; corps; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; régions géographiques; sexe/genre; shm4000; systèmes d'oppressions; thématiques; transféminisme

Sexes et pouvoir : la construction sociale des corps et des émotions - Préjean, Marc (Presses de l'Université de Montréal, 1994)
Keywords: 1900-1999; 1990-1999; amériques; care; corps; cours; différence des sexes; discipline; fem1000; militance; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sociologie; thématiques; émotions

Des outils pour écrire le corps - Centre de création industrielle (Paris); Centre national d'art et de culture Georges Pompidou (Paris); de Certeau, Michel (Traverses, 1993)
Publisher: Centre Georges Pompidou
Keywords: corps; cours; discipline; lit4700; premier cycle; sciences humaines; sociologie; sofia; thématiques

La fabrique du sexe : essai sur le corps et le genre en Occident - Laqueur, Thomas Walter (Gallimard, 1992)
L'Occident n'a cessé depuis les origines de s'interroger sur la différence des sexes. Mais parle-t-on de l'homme et de la femme que l'on n'a encore rien dit : se réfère-t-on au genre - définition culturelle par des qualités morales, affectives, sociales... - ou au sexe - définition par des spécificités anatomiques ? Jamais, en effet, les deux notions ne se recouvrirent, rappelle Thomas Laqueur dans cet ouvrage qui demeure une référence majeure. Dès l'Antiquité, Aristote, par la définition de l'ordre des êtres, et Galien, par la définition du corpus anatomique, fondent le modèle du sexe unique, qui sera dominant jusqu'au XVIIIe siècle, et dans lequel le genre définit le sexe. Au XVIIIe siècle émerge l'autre modèle de la différence sexuelle, le modèle des deux sexes, dans lequel, au contraire du premier, le sexe définit le genre : parce que, au niveau de l'anatomie comme de la physiologie, femmes et hommes sont incommensurablement différents, les genres définissent dès lors qualités, vertus et rôles selon des racines biologiques. Ces deux modèles coexistent dans le temps - dès le XVIe siècle des auteurs posent l'irréductible différence anatomique, alors qu'au XXe siècle encore Freud pense la sexualité selon le modèle du sexe unique - car leur prégnance sur les esprits, si elle est liée à des évolutions générales - économiques, culturelles, sociales -, ne peut en aucun cas être strictement expliquée par celles-ci; et moins encore par les progrès de la connaissance anatomique, qui se moulent le plus souvent dans les représentations dictées par chacun de ces modèles...
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; corps; cours; discipline; discours dominant; essentialisme; féminisme matérialiste; genre; histoire; histoire et politique; hétérosexisme; occident; philosophie politique; premier cycle; production des savoirs; périodes historiques; sciences humaines; sciences sociales; sex1183; sex3383; sexe/genre; sexualité; systèmes d'oppressions; thématiques; épistémologie

The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

From mastery to analysis: Theories of gender in psychoanalytic feminism - Elliot, Patricia (Cornell University Press, 1991)
Critique des approches psychanalytiques en études féministes et de l'hystérie (Kristeva, Irigaray, Chodorow, Dinnerstein, Mitchell, Lacan, Freud) Voir le compte-rendu: Williams, C. L. (1992). [Review of From Mastery to Analysis: Theories of Gender in Psychoanalytic Feminism., by P. Elliot]. Contemporary Sociology, 21(5), 728–729. https://doi.org/10.2307/2075599
Keywords: 1900-1999; corps; cours; discipline; europe; fem1000; france; maternité; premier cycle; psychanalyse; périodes historiques; royaume-uni; régions géographiques; sciences; sciences humaines; sexualité; thématiques

Journal de la création - Huston, Nancy (Seuil, 1990)
Pendant des millénaires, tout paraissait simple : aux hommes la création, aux femmes la procréation ; aux hommes l'esprit et aux femmes le corps. L'émancipation féminine a bousculé cette distribution des rôles et mis à mal des métaphores séculaires : la muse féminine, l'œuvre d'art comme amante ou comme " enfant " de l'artiste. Mais trouver un nouveau modus vivendi n'est pas facile pour autant. Mettant à profit une certaine et curieuse forme de clairvoyance liée, dans son esprit, aux métamorphoses de son corps de femme enceinte, Nancy Huston s'est penchée sur les histoires souvent douloureuses de Sand et Musset, Virginia et Leonard Woolf, Scott et Zelda Fitzgerald, Sartre et Beauvoir. Le récit de ses recherches sur les couples d'écrivains et le journal de sa propre grossesse se croisent, se répondent et se complètent pour évoquer les mystères de l'amour, de l'inspiration, du couple et de la création.
Donné en lecture: p.11-56
Keywords: 1900-1999; 1980-1989; amériques; corps; cours; discipline; europe; fem1000; lit2815; lit3220; lit3495; littérature; maternité; premier cycle; périodes historiques; régions géographiques; thématiques; études culturelles; études littéraires